2019
DOI: 10.1177/0267659119874696
|View full text |Cite
|
Sign up to set email alerts
|

The successful use of extra-corporeal membrane oxygenation as rescue therapy for unilateral pulmonary edema following minimally invasive mitral valve surgery

Abstract: Unilateral right pulmonary edema has been reported as a potential life-threatening complication after minimally invasive mitral valve surgery. Nearly 2% of these cases in the immediate postoperative period have been reported to require extra-corporeal membrane oxygenation support as a rescue therapy for severe hypoxia. The exact pathophysiology of this condition remains unclear, but has been assumed to be related to ischemia–reperfusion injury and re-expansion pulmonary edema. We present in this report the suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…MODS is a progressive and potentially reversible dysfunction of at least two organ systems in the course of the acute and life-threatening disorder of systemic homeostasis [ 4 , 5 ]. The mechanical support of organs, such as hemodiafiltration in the case of renal failure, mechanical ventilation in the case of respiratory failure, or mechanical circulatory support with the use of intra-aortic balloon pump (IABP) and extracorporeal membrane oxygenation (ECMO), can correct the physiological state of a patient in the multi-organ failure syndrome, improving oxygen supply to peripheral tissues and tissue metabolism, while providing the necessary time for the regeneration of individual organs, such as a central nervous system, kidneys, lungs, and heart [ 6 , 7 , 8 , 9 , 10 ]. Knowledge of the predictors of MODS occurrence in the postoperative period is essential because it can inform the preoperative selection of patients at increased risk of this complication and special care for selected patients during the perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“…MODS is a progressive and potentially reversible dysfunction of at least two organ systems in the course of the acute and life-threatening disorder of systemic homeostasis [ 4 , 5 ]. The mechanical support of organs, such as hemodiafiltration in the case of renal failure, mechanical ventilation in the case of respiratory failure, or mechanical circulatory support with the use of intra-aortic balloon pump (IABP) and extracorporeal membrane oxygenation (ECMO), can correct the physiological state of a patient in the multi-organ failure syndrome, improving oxygen supply to peripheral tissues and tissue metabolism, while providing the necessary time for the regeneration of individual organs, such as a central nervous system, kidneys, lungs, and heart [ 6 , 7 , 8 , 9 , 10 ]. Knowledge of the predictors of MODS occurrence in the postoperative period is essential because it can inform the preoperative selection of patients at increased risk of this complication and special care for selected patients during the perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“…It is often difficult to clarify the etiology of this challenging condition because NCPE is multifactorial. To our knowledge, cases of fulminating NCPE following cardiac surgery which require ECMO are associated with transfusion-related lung injury (TRALI) [ 7 , 8 ], re-expansion pulmonary edema [ 2 , 5 , 6 ] and protamine-induced pulmonary edema [ 9 , 10 ]. In Case 1, the main etiology of alveolar flooding was speculated to be TRALI, although re-expansion of the lungs and protamine administration were also possible causes because all these events occurred during the limited time frame soon after CPB termination.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in Case 2, re-expansion pulmonary edema was highly suspected as the main etiology because there were no other potential factors, such as blood transfusion and protamine administration, when frothy sputum was expelled through the tracheal tube. It has been reported that re-expansion of pulmonary edema often occurs after MICS, with an incidence rate of 2.1% [ 12 ], and in some cases, the patients were successfully treated with VV-ECMO [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of ECMO should be considered at an early stage of treatment in a haemodynamically unstable patient after heart valve surgery if that patient has low systolic pressure, low cardiac output, and, as a consequence, insufficient tissue perfusion in which clinical stabilization is not achieved despite the use of conservative treatment in combination with the use of catecholamines [ 6 , 22 ]. The administration of oxygenated blood to the arterial system with appropriate kinetic energy, generated by the ECMO pump, ensures the adequate perfusion of peripheral tissues and relieves the heart muscle by promoting its regeneration [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%